Effect of Different Combinations of Nitrogen, Phosphorus and Potassium on Growth and Yield of Okra (Abelmoschus esculentus L.) under Rupandehi Condition - Silwal, Swasthani; Acharya, Sujata; Sangpang, Devesh Rai; Chalaune, Nabin; Mandal, Jawahar Lal; Pathak, Rukmagat; Poudel, Puspa Raj (Journal of the Institute of Agriculture and Animal Science, 2023)
An experiment on effect of different combinations of nitrogen, phosphorous and potassium on growth and yield of okra (Abelmoschus esculentus L.) var. ArkaAnamika was conducted at Institute of Agriculture and Animal Science (IAAS), Paklihawa, Rupandehi during February 2017 to June 2017. The experiment was laid in Randomized Complete Block Design (RCBD) with seven treatments and three replications. The treatments 220:200:60 NPK Kg ha–1 (T1), 200:180:60 NPK Kg ha–1 (T2), 180:160:40 NPK Kg ha–1 (T3), 160:140:40 NPK Kg ha–1 (T4), 140:120:20 NPK Kg ha–1(T5), 120:100:20 NPK Kg ha–1 (T6) and Control (T7) were applied and the growth, yield and yield attributes of okra were studied. The result revealed that there were no significant differences (p=0.05 level by Duncan’s Multiple Range Test-DMRT) on plant height, number of leaves, number of branches, fruit length, fruit diameter, average number of fruit per plant and average marketable yield to the effect of different combination of NPK levels. However, the result showed that average marketable yield and total yield was found significant over the control and also the highest total yield (43.21 Mt/ha) was obtained at 160:140:40NPK Kg ha–1.